Hourcquia Collignon, 1965 (Cretaceous Ammonoidea) from the upper Turonian of the southern United States - Kennedy, W; Cobban, W; Hook, S (1988)
Hourcquia Collignon, 1965, previously described only from the upper Turonian of Madagascar, Venezuela, South Saghalien and Hokkaido, Japan, is documented from New Mexico and Texas in the United States. The material is referred to a single variable species, H. mirabilis Collignon, 1965, previously known only from Madagascar and Hokkaido, Japan. © 1988 E. Schweizerbart'sche Verlagsbuchhandlung.